Public and Private Education: Conceptualizing the Distinction - Bidwell, Charles E.; Dreeben, Robert (Catholic Education: A Journal of Inquiry and Practice, 2003)
Common wisdom and public discourse seem to suggest that there are two types of schools, private and public. Policy debates, media outlets, and comparisons of outcomes on standardized tests and interscholastic athletic competitions make use of the distinction. This essay argues that while such a distinction can be helpful, it also tends to obscure differences in the social organization of schools. Employing a sociological analysis and providing a historical overview of educational developments, the authors focus on centralization versus decentralization of school controls and discuss the ramifications of a broad versus a narrow market niche for schools.